EKONOMI ISLAM DAN KEARIFAN LOKAL - Rahmani Timorita Yulianti (Millah: Journal of Religious Studies, 2010)
Indonesia is an archipelago which has a diverse system of cultural customs of the archipelago. With so much local wisdom in it. Related to the system and the economic behavior of the Indonesian people, whether in the traditional system of culture of the archipelago there is an economic system that is still practiced by the community? What is the economic system there are indigenous cultures of the archipelago is relevant to the economic principles of Islam? Therefore, space exploration and assessment of local knowledge into separate claims for one of the methods of economic development of Islam in Indonesia. Responding to the scientific development of new discourse of Islamic economics, the paper seeks to discuss further on, (1) What are the sources of Islamic economic law that allows synergy between Islamic economics and local wisdom?, (2) How is the meeting point ‘urf and local wisdom, and (3) How can tolerance towards indigenous Islamic economics?